Penerapan Asas Keadilan Restoratif (Restorative Justice) dalam Penyelesaian Tindak Pidana Penganiayaan Ringan - Doni Sugiri; Aturkian Laia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The surge in caseloads and criticism of punitive imprisonment have driven the development of restorative justice in Indonesia. Minor assault is a potential case for this approach due to its low impact and the possibility of restoring social relations. This normative legal research aims to analyze the legal basis, implementation mechanisms at each stage of adjudication, effectiveness of justice, and implementation barriers of minor assault through statutory and conceptual approaches. The results indicate that minor assault is normatively and practically suitable for restorative settlement, provided it meets criteria such as voluntary peace, restitution, and non-recidivism. This approach supports modern sentencing goals through rehabilitation, process efficiency, and reduced stigmatization. However, implementation is hindered by disharmony in sectoral regulations, varying interpretations among law enforcers, and potential imbalances in victim bargaining power. Therefore, standardized procedures and strict oversight are essential to ensure just, secure, and accountable law enforcement.